Evaluation of Carbon-Coated Graphite as a Negative Electrode Material for Li-Ion Batteries - Varvara Sharova; Arianna Moretti; Guinevere A. Giffin; Diogo Vieira Carvalho; Stefano Passerini (C, 2017)
Low-cost and environmentally-friendly materials are investigated as carbon-coating precursors to modify the surface of commercial graphite for Li-ion battery anodes. The coating procedure and final carbon content are tuned to study the influence of the precursors on the electrochemical performance of graphite. Thermogravimetric analysis (TGA) and Brunauer–Emmett–Teller (BET) surface area analysis are used to characterize the carbon coating content and the surface area, respectively, whereas X-ray diffraction (XRD) and Raman spectroscopy allow tracking of the graphite’s structural changes and surface amorphization. In general, the coating reduces the first cycle coulombic efficiency by 3%–10% compared to pristine graphite due to the increase of the surface area available for the continuous electrolyte decomposition. However, the use of citric acid as a carbon source (5 wt %) improves the rate capability of graphite, resulting in the specific delithiation capacity at 3C of 228 mAh g−1 vs. 211 mAh g−1 for the uncoated graphite. The attempt to reduce the coating amount from 5 wt % to 2 wt % results in a lower rate capability, but the first cycle coulombic efficiency is similar to that of pristine graphite.